Chemical Composition of the Leaf Oil of Cymbopogon martinii var. sofia Collected from Udaipur, Rajasthan and their Screening Against Fungi Causing Dermatophytosis in Human Beings. Issue 3 (4th May 2017) - Jain, Neetu; Sharma, Meenakshi
Abstract: Cymbopogon martinii var. sofia an important medicinal plant, was collected from forest nursery Udaipur, Rajasthan, India. Plant is very known among local tribal and sub-tribal community due to their medicinal importance. Oil was extracted through hydrodistillation method using Clevenger's apparatus. GC/GC-MS analysis of C. martinii essential oil exhibited presence of 37 compounds. The major constituents were sabinol (19.19 %), trans -p-mentha-2, 8-dienol (18.67 %), trans -carveol (18.27 %), cis -p-mentha-2, 8-dien-1-ol (11.11 %), cis -carveol (7.66 %), delphone (7.47 %), carvone (3.72 %), durenol (3.01 %), limonene (1.76 %) and camphene (1.59 %). Antidermatophytic activity of C. martinii leaves essential oil was carried out against selected dermatophytic fungi and Candida albicans using disc diffusion technique and by minimum inhibitory concentration determinations. Maximum 80.67±0.289 mm inhibition zone and activity index 3.2 was observed against Trichophyton mentagrophytes (MTCC 7687) followed by 78.33±1.527 mm against M. fulvum (MTCC 2837) and 45.5±0.500 mm against T. rubrum (MTCC 296). Minimum inhibitory concentration was ranged from 2 μl/ml to 3 μl/ml against tested fungi. Present study concluded that essential oil of Cymbopogon martinii Var. Sofia have strong antimicrobial properties.